2017
DOI: 10.1055/s-0043-121150
|View full text |Cite
|
Sign up to set email alerts
|

A functional MRI Exploration of Hamstring Activation During the Supine Bridge Exercise

Abstract: The single leg supine bridge (SLB) is a commonly employed strengthening exercise and is used as a clinical test for hamstring function in sports, however, little is known about the patterns of muscle activation in this task. To explore these activation patterns, nine healthy, recreationally active males underwent functional magnetic resonance imaging (fMRI) of their thighs at rest and immediately after 5 sets of 10 repetitions of the SLB exercise. Exercise-induced increases in the transverse (T2) relaxation ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…On the contrary, hamstrings activity was particularly high in SB. In the current study, we did not detect clear differences between muscles in SB, contrary to Bourne et al who found higher metabolic activity in ST compared to BFlh, although the between‐muscle difference seems to be smaller compared to most of the other exercises previously examined with mfMRI . These discrepancies may arise from methodological issues: both mfMRI and EMG have limitations when comparing the relative contribution of different hamstring muscles.…”
Section: Discussioncontrasting
confidence: 99%
“…On the contrary, hamstrings activity was particularly high in SB. In the current study, we did not detect clear differences between muscles in SB, contrary to Bourne et al who found higher metabolic activity in ST compared to BFlh, although the between‐muscle difference seems to be smaller compared to most of the other exercises previously examined with mfMRI . These discrepancies may arise from methodological issues: both mfMRI and EMG have limitations when comparing the relative contribution of different hamstring muscles.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, an increased frequency of superimposed vibration on the suspension straps (> 40 Hz) and performing the exercise unilaterally, single-leg suspended supine bridge, could increase the demand of the biceps femoris to high activations (> 41% MVIC), as indicated by previous studies on sEMG on the single-leg supine bridge on the floor ( Lehecka et al, 2017 ), or on a BOSU ( Youdas et al, 2015 ). In this vein, the functional magnetic resonance imaging study conducted by Bourne et al (2018b) found a predominant activation of the biceps femoris long head. Likewise, there could be several reasons for the small differences between the biceps femoris and semitendinosus in the suspended supine bridge.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, the biceps femoris long head and other biarticular hamstrings appear to be more active during a 45°hip extension exercise than the Nordic exercise [23]. In addition, the long head of biceps femoris appears to be significantly more active than its short head during a single-leg supine bridge exercise [80]. Furthermore, Mendiguchia and colleagues have observed elevated T2 values in the proximal but not middle or distal portions of biceps femoris long head after a lunge exercise [25].…”
Section: Patterns Of Hamstring Muscle Activationmentioning
confidence: 97%